Managing climate change challenges to water security: Community water governance in Ethiopia and Nepal - Adrian Flint; Guy Howard; Anisha Nijhawan; Moti Poudel; Abraham Geremew; Yohannes Mulugeta; Eunice Lo; Anish Ghimire; Manish Baidya; Subodh Sharma (Geo: Geography and Environment, 2024)
Abstract Climate change poses a threat to water security where both current and future generations are concerned, with its accompanying impacts set to be greater in low‐ and middle‐income countries (LMICs). As a result, questions pertaining to climate change adaption in LMICs are receiving increased attention from academics and policymakers alike. It is broadly accepted that top‐down approaches to developing resilience to climate change challenges have been shown to be limited and that concerted efforts need to be made to engage local communities in advancing adaptive strategies. Based on the above, we make two main arguments: (1) while there has been a shift towards acknowledging the importance of community‐driven data in generating a broader and deeper understanding of climate change, far better use could be made of local knowledge and (2) efforts at community‐based solutions to problems of resilience are currently limited by issues of capacity, specifically linked to the need for further education and training, and improved representation with respect to gender, class and caste (as well as financial support). To illustrate these arguments, we present evidence provided by rural communities located in two countries affected heavily by climate change: Ethiopia and Nepal.